High-resolution ultrasound in ulnar neuropathy at the elbow: A prospective study - Ellegaard, Hanne R.; Fuglsang-Frederiksen, Anders; Hess, Alexander; Johnsen, Birger; Qerama, Erisela (Muscle & nerve, 2015)
ABSTRACT Introduction We examined the role of ultrasound in diagnosing and localizing ulnar neuropathy (UN) at the elbow. Methods Forty‐one patients referred for UN and 43 healthy subjects were included. Cross‐sectional area (CSA) of the ulnar nerve was measured by ultrasound at 5 locations across the elbow and at the wrist. Patients underwent near‐nerve conduction studies (N‐NCS). Results Ultrasound (US) had a sensitivity of 80.5%, N‐NCS had a sensitivity of 70.7%, and combined sensitivity was 85.4% in diagnosing UN. Using N‐NCS as a reference standard, US reached a sensitivity of 93.1% and a specificity of 50.0% in diagnosing UN, and a sensitivity of 77.3% and a specificity of 42.9% in localizing UN at the elbow. There was a reduction in mean CSA at 3‐month follow‐up. Conclusions N‐NCS and US are complementary methods and have the potential to increase the sensitivity for diagnosing and localizing UN at the elbow. Muscle Nerve 52: 759–766, 2015